The horn bases of the Reedbuck Redunca arundinum - H. Jungius; C.P. Claussen; W. Germany (Koedoe: African Protected Area Conservation and Science, 1975)
The structure and function of the horn bases of the reedbuck Redunca arundinum are discussed. It is shown that the white colouration which often occurs is not caused by glandular secretion but by small horn particles which are shed, exposing the lighter coloured material underneath. The shining horn base probably plays a role in the display behaviour of males.